Republic of Croatia : Report on Observance of Standards and Codes-Fiscal Transparency Module. (IMF Staff Country Reports; Country Report ;, 2004)
This report examines the Observance of Standards and Codes on Fiscal Transparency for Croatia. The assessment reveals that Croatia meets the fiscal transparency code in a number of areas and has been making significant progress in strengthening fiscal management and transparency. The allocation of responsibilities among different levels of government generally has been well defined, and stable intergovernmental fiscal relations have been established. The Budget Act of 2003 has significantly strengthened the legal framework for budget management. The establishment of a single treasury account has also improved controls over budget execution.